OLEMACH THEOREM: ANGULAR-MOMENTUM CONSERVATION IMPLIES GRAVITATIONAL-REDSHIFT PROPORTIONAL CHANGE OF LENGTH, MASS AND CHARGE - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
There is a minor revolution going on in general relativity: a “return to the mothers“ – that is, to the equivalence principle of Einstein. Recently, the Telemach theorem was described. Here now, the completely independent but fully convergent “Olemach theorem” is introduced. It connects omega (rotation rate), length, mass and charge in a static field. The predictable consequence of the two theorems is a return to the hard core of general relativity at the expense of some peripheral features. A connection to cosmology is mentioned along with a promising technological development.